(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores strategies for preserving emotional nuances and persuasive rhetorical techniques in translating psychological and motivational literature from English into Uzbek. The comparative analysis focuses on Jeyms Klir’s Atomic Habits, Stephen R. Kovi’s The 7 Habits of Highly Effective People, and Robert Kiyosaki’s Rich Dad Poor Dad along with their Uzbek translations. Specific translation strategies such as dynamic equivalence, calque, modulation, and cultural adaptation were examined to assess how effectively emotional tone, personal anecdotes, and persuasive rhetoric (ethos, logos, pathos) are maintained. The study demonstrates that the translators effectively preserved the original texts’ emotional impact and rhetorical features, successfully generating responses in Uzbek readers comparable to those experienced by the original audience.